2022-RA-881-ESGO Introduction of a sentinel lymph node protocol for endometrial cancer at a regional cancer center in UK. (20th October 2022) - Mohamed AlWahaibi, Fatma; McCorkindale, Emma; Nagar, Hans; Dobbs, Stephen; McComiskey, Mark; Craig, Elaine; Harley, Ian
Abstract : Introduction/Background: Lymphadenectomy in endometrial cancer (EC) is one of the controversial topic in gynecologic oncology. Sentinel lymph node (SLN) has become a popular option in the last few years .Belfast City Hospital – Regional Cancer Center in United Kingdom started using SLN since 2021. The aim of this study is to develop a protocol for SLN to standardize the practice in the center. Methodology: Retrospective cohort of EC patients with apparently early stage EC undergoing surgical staging with SLN were analyzed from January 2021 onward . All patients with high grade, early stage EC were included .The primary outcome was to assess the overall, bilateral successful and unsuccessful SLN mapping. Secondary outcome was identifying the predictors for mapping failure and adverse events. Results: Total of 286 patients with EC diagnosed since January 2021 were analyzed. Seventeen patients were diagnosed as high grade, early stage of EC. However, two were morbidly obese and unfit for SLN. Mean age 69.4 range (53–81 years) including 7 patients with high grade endometrioid adenocarcinoma, 4 with carciosarcoma, 3 with serous carcinoma and 1 with clear cell carcinoma. Mean body mass index (BMI) was 27.5 (calculated as weight in Kilogram divided by height in meters squared) range (22–36). Regarding detection rate; the successful bilateral mapping, at least successful unilateral mapping and the mapping failure of SLN (60%, 80%, 20%) respectively. No major adverse events were recorded. The advanced age affects the anatomical distribution of SLN. Non endometrioid histotype and lymph vascular space invasion (LVSI) represent independent predictor of unsuccessful mapping. Conclusion: SLN is an available option for surgical staging of EC with markedly less complications compared to full lymphadenectomy . We consider all the major factors which might cause failure of SLN during preparation of a protocol in our center.